On Pentagonal Controlled Fuzzy Metric Spaces with an Application to Dynamic Market Equilibrium. (11th January 2022) - Hussain, Aftab; Ishtiaq, Umar; Ahmed, Khalil; Al-Sulami, Hamed
Abstract : In this manuscript, we coined pentagonal controlled fuzzy metric spaces and fuzzy controlled hexagonal metric space as generalizations of fuzzy triple controlled metric spaces and fuzzy extended hexagonal b-metric spaces. We use a control function in fuzzy controlled hexagonal metric space and introduce five noncomparable control functions in pentagonal controlled fuzzy metric spaces. In the scenario of pentagonal controlled fuzzy metric spaces, we prove the Banach fixed point theorem, which generalizes the Banach fixed point theorem for the aforementioned spaces. An example is offered to support our main point. We also presented an application to dynamic market equilibrium.